(untitled) - Thomson, Dixon (Gabriola Island, 2002)
Corporations, governments and other institutions need a systematic approach to meeting their environmental obligations, goals, and objectives -- no matter whether they are driven by government regulations, public relations, and/or a commitment to conserving resources and preserving the environment. This book provides a Tool Box and the concepts and principles necessary for designing, implementing, and operating an effective environmental management system.
Quản lí môi trường và công nghệ sạch
Keywords: Environmental management,Quản trị môi trường